2009
DOI: 10.1016/j.neuropharm.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate transmission in addiction

Abstract: Cortico-striatal glutamate transmission has been implicated in both the initiation and expression of addiction related behaviors, such as locomotor sensitization and drug seeking. While glutamate transmission onto dopamine cells in the ventral tegmental area undergoes transient plasticity important for establishing addiction-related behaviors, glutamatergic plasticity in the nucleus accumbens is critical for the expression of these behaviors. This information points to the value of exploring pharmacotherapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
270
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(280 citation statements)
references
References 76 publications
9
270
0
1
Order By: Relevance
“…Results from the present study are consistent with literature implicating plastic changes in multiple nodes of the brain reward network in the development, maintenance, and/ or resumption of substance use (Baler and Volkow, 2006;Kalivas and O'Brien, 2008;Kalivas et al, 2009;McFarland et al, 2003;Sher et al, 2005;Volkow and Fowler, 2000;Volkow et al, 2001Volkow et al, , 2004. The overall pattern of results from the present study parallels the morphological fi ndings by Wrase and colleagues (2008), who observed lower amygdala volume in alcohol-dependent individuals who relapsed after treatment, compared with those who remained abstinent and relative to controls (the amygdala is a crucial component of the brain reward system involved in the determination of the emotional valence of a stimulus; Kalivas and Volkow, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Results from the present study are consistent with literature implicating plastic changes in multiple nodes of the brain reward network in the development, maintenance, and/ or resumption of substance use (Baler and Volkow, 2006;Kalivas and O'Brien, 2008;Kalivas et al, 2009;McFarland et al, 2003;Sher et al, 2005;Volkow and Fowler, 2000;Volkow et al, 2001Volkow et al, , 2004. The overall pattern of results from the present study parallels the morphological fi ndings by Wrase and colleagues (2008), who observed lower amygdala volume in alcohol-dependent individuals who relapsed after treatment, compared with those who remained abstinent and relative to controls (the amygdala is a crucial component of the brain reward system involved in the determination of the emotional valence of a stimulus; Kalivas and Volkow, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…47,48 More recently, data are emerging suggesting a role of oxidative stress in the pathophysiology of addiction to drugs of abuse. 32,[49][50][51] Research has explored the modulation of glutamatergic pathways by NAC in preclinical models.…”
Section: Addictionmentioning
confidence: 99%
“…Drugs of abuse such as amphetamine and cocaine usurp this basic function, essentially hijacking the circuitry via induction of maladaptive plasticity (Kauer and Malenka 2007;Kalivas et al 2009;Chen et al 2010;Russo et al 2010; Van den Oever et al 2010;Badiani et al 2011;Luscher and Malenka 2011;Sulzer 2011). As mentioned above, the dopaminergic mesolimbic pathway and its associated neuroanatomical structures are heavily implicated in drug-induced neuropathology ( Fig.…”
Section: Basic Neuroanatomy Of Reward Circuitrymentioning
confidence: 99%